Impact of #PsychTwitter in promoting global psychiatry: A hashtag analysis study - Faisal A. Nawaz; Mehr Muhamad Adeel Riaz; Christos Tsagkaris; Umme H. Faisal; Elisabeth Klager; Maria Kletecka-Pulker; Maria Kletecka-Pulker; Oliver Kimberger; Oliver Kimberger; Harald Willschke; Harald Willschke; Nagina Khan; et al. (Frontiers Media S.A., 2023)
IntroductionMultiple studies have shown how valuable Twitter hashtags can be for promoting content related to different themes in the online community. This arena has grown into a rich data source for public health observation and understanding key trends in healthcare on a global scale. In the field of mental health in particular, it would be of benefit to understand and report the key stakeholders' (individual mental health professionals, academic organizations and their countries) trends and patterns of psychiatric knowledge and information dissemination using #PsychTwitter.ObjectiveIn this study, we aim to evaluate the achieved outreach of psychiatry-related tweets using the hashtag #PsychTwitter.MethodsWe utilized the Symplur Signals research analytics tool to characterize tweets containing #PsychTwitter from the 20th of August, 2019, to the 20th of August, 2022.ResultsThe #PsychTwitter movement resulted in 125,297 tweets that were shared by 40,058 Twitter users and generated a total of 492,565,230 impressions (views). The three largest identified groups of contributors were Doctors (13.8% of all tweets), Org. Advocacy (6.2% of all tweets), and Researcher/Academic (4% of all tweets) stakeholders. The top influential accounts consisted of 55 psychiatrists and 16 institutional or organizational accounts. The top 5 countries from where most of the tweets containing #PsychTwitter were shared include the United States (54.3% of all users), the United Kingdom (10.4% of all users), Canada (4.9% of all users), India (2% of all users), and Australia (1.8% of all users).ConclusionThis is the first of its kind study featuring the influence and usage of #PsychTwitter and covering its global impact in the field of psychiatry using the Twitter platform. Our results indicate that Twitter represents a broadly used platform for mental health-related discussions.